Helping patient educators meet health literacy needs: End-user testing and iterative development of an innovative health literacy editing tool - Ayre, Julie; Muscat, Danielle M.; Mac, Olivia; Bonner, Carissa; Dunn, Adam G.; Dalmazzo, Jason; Mouwad, Dana; McCaffery, Kirsten (PEC innovation, 2023)
The Sydney Health Literacy Lab (SHeLL) Editor is an online text-editing tool that provides real-time assessment and feedback on written health information (assesses grade reading score, complex language, passive voice). This study aimed to explore how the design could be further enhanced to help health information providers interpret and act on automated feedback. The prototype was iteratively refined across four rounds of user-testing with health services staff (N = 20). Participants took part in online interviews and a brief follow-up survey using validated usability scales (System Usability Scale, Technology Acceptance Model). After each round, Yardley's (2021) optimisation criteria guided which changes would be implemented. Participants rated the Editor as having adequate usability (M = 82.8 out of 100, SD = 13.5). Most modifications sought to reduce information overload (e.g. simplifying instructions for new users) or make feedback motivating and actionable (e.g. using frequent incremental feedback to highlight changes to the text altered assessment scores). terative user-testing was critical to balancing academic values and the practical needs of the Editor's target users. The final version emphasises actionable real-time feedback and not just assessment. The Editor is a new tool that will help health information providers apply health literacy principles to written text. •Existing health literacy tools do not provide actionable real-time objective feedback.•The SHeLL Editor provides instant automated feedback on written health information.•We tested the Editor with health staff to identify how it could be further improved.•The SHeLL Editor was rated high on usability and acceptability by health staff.•Key changes were simplifying the user interface and ensuring feedback was actionable.